A comparative study between the Brazilian cooperativism and world reference countries - Biscaro, Chrystian; Luzio-dos-Santos, Luis Miguel; Hernandes, Juliana Fatima de Moraes (Cooperativismo & Desarrollo, 2023)
Cooperativism emerged in the nineteenth century, in England, as a response to the deleterious consequences of the accelerated development of industrial capitalism. It was founded to resist the hegemony of big business, which already demonstrated its contradictions and strong exploitation of the working class. Cooperativism, a term interchangeable with the expression cooperative movement, can be understood as a socio-productive system based on cooperative organizations, but not limited to them, as it goes beyond the productive universe and incorporates a set of societal values, as participation and mutual responsibility. Given its organizational plurality and geographic scope, this study aims to analyze the Brazilian cooperative model in comparison to the models: New Zealand, French, Finnish and Italian, seeking to bring out similarities and differences, barriers and potential for the development of Brazilian cooperativism. The selection of these countries is due to the fact that they are among the main highlights in the Cooperative Economy Index according to the UN. It is a qualitative and descriptive research, fundamentally based on journals, scientific studies and relevant international research on the subject. As a result of the research, it was found that Brazilian cooperativism still presents timid indicators in relation to reference countries in the area, which points to a vast field to be developed. On the other hand, with regard to the movement’s structure, the country follows the best global practices, with a body responsible for representing and bringing together the movement’s interests, which creates greater unity and strength for the movement. It is also in tune with reference countries in terms of principles and values, notably solidarity, responsibility, democracy and equality.